Estaquia de Luehea divaricata Mart. (Açoita-cavalo) - Pacheco, Jardel Pizzatto (2007)
Three experiment was carried out to evaluate the influence of indolbutyric acid (IBA), substrate and type of stem cutting on the rooting of Luehea divaricata. The first study was evaluated the effect of diameter stem cutting and IBA in the adventitious rooting. Woody stem cuttings were used, of plant matrices with approximately ten years age, distributed as the diameter (fine, medium, thick) and level of IBA (0, 5000 mg L-1). The experimental design was completly randomized and consisting of 12 units experimental by repetition and five repetitions for treatment. There was no interaction of the diameter and IBA for the variables survival, length and number of roots. There was, however, interaction for the number of root. There was no influence of diameter on the number of roots in Luehea divaricata. Thick stem cuttings showed higher survival, rooting and length of root than smaller diameter. The survival of stem cuttings was not influenced by indolbutyric acid. Stem cutting treated with 5000 mg L-1 IBA showed higher roots, number and length of roots of then control treatment. Thick stem cuttings immersed at 5000 mg L-1 of IBA are indicated in the vegetative propagation of Luehea divaricata. The secon study was evaluated the effect of type of stem cutting and IBA in the rooting of this specie. Woody stem cuttings were used, of plant matrices with approximately two years age, distributed as the position (basal, middle, apex) and level of IBA (0, 1000, 2000, 5000 mg L-1). The experimental design was completly randomized and consisting of five units experimental by repetition and five repetitions for treatment. There was no interaction between position and IBA for the variables rooting and number of roots. There was, however, interaction for the leaf and root dry mass. The position presented influence in all variables, being observed on basal cuttings higher rooting, number of roots, leaf and root dry mass. The variable leaf dry mass was not influenced by the application of indolbutyric acid. Stem cuttings with 4000 mg L-1 of IBA had higher rooting and number of roots. Moreover, was observed higher values root dry mass in stem cuttings with 2000 mg L-1 indolbutyric acid. The third study was evaluated the effect of type of stem cutting and substrate in the rooting of Luehea divaricata. Herbaceous stem cuttings were used, of plant matrices with approximately two years age, distributed as the type of stem cutting (with / without leaf) and type of substrate (vermiculite, mecplant®, plantmax®, peat). The experimental design was completly randomized and consisting of five units experimental by repetition and 10 repetitions for treatment. There was no interaction between substrate and type of stem cutting for the variables rooting and number of roots. There was, however, interaction for root length, root and leaf dry mass. The type of stem cutting presented influence in all variables studied. Stem cuttings grown on peat and Plantmax® showed higher root length, root and leaf dry mass. Stem cuttings with a pair of leaf grown in Plantmax® are indicated in the vegetative propagation of Luehea divaricata.